2004
DOI: 10.1074/jbc.m404611200
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Mutagenesis of the Farnesylation Site of Drosophila Gγe Disrupts Membrane Association of the G Protein βγ Complex and Affects the Light Sensitivity of the Visual System

Abstract: Activation of phototransduction in the compound eye of Drosophila is mediated by a heterotrimeric G protein that couples to the effector enzyme phospholipase C␤. The ␥ subunit of this G protein (G␥e) as well as ␥ subunits of vertebrate transducins contain a carboxyl-terminal CAAX motif (C, cysteine; A, aliphatic amino acid; X, any amino acid) with a consensus sequence for protein farnesylation. To examine the function of G␥e farnesylation, we mutated the farnesylation site and overexpressed the mutated G␥e in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 49 publications
(40 reference statements)
0
16
0
Order By: Relevance
“…The effector for the light-activated rhodopsin is the heterotrimeric G-protein, G q and it is encoded by Gα q [108][109][110], Gβ e [111,112], and Gγ e [113,114], all of which are eyeenriched. After exchange of the guanosine diphosphate (GDP) bound to the Gα q for GTP, the Gα q and Gβγ subunits dissociate and the activated Gα q -GTP binds to the PLC encoded by norpA (no receptor potential A) [5,115].…”
Section: G Q Protein In Phototransductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effector for the light-activated rhodopsin is the heterotrimeric G-protein, G q and it is encoded by Gα q [108][109][110], Gβ e [111,112], and Gγ e [113,114], all of which are eyeenriched. After exchange of the guanosine diphosphate (GDP) bound to the Gα q for GTP, the Gα q and Gβγ subunits dissociate and the activated Gα q -GTP binds to the PLC encoded by norpA (no receptor potential A) [5,115].…”
Section: G Q Protein In Phototransductionmentioning
confidence: 99%
“…A strong allele of Gβ e mutant, Gβ 1 e , displays a ∼100-fold reduction in light sensitivity [111], and a mutation in the farnesylation site of Gγ e also results in a reduction in light sensitivity [114]. Moreover, light-simulated PLC activity is deficient in the Gβ 1 e mutant [116].…”
Section: G Q Protein In Phototransductionmentioning
confidence: 99%
“…Functional characterization of four independent 35S-γ ⁎ lines has consistently shown that they behave in the same way as α-and β-deficient mutants, albeit with less severity. The reduction of severity was predicted as a possible outcome of our approach, which is not as dominant in nature as the complete α or β knockouts and was also observed in a similar study using Drosophila (Schillo et al, 2004). Expression levels of the endogenous AGG1 and AGG2 genes are unchanged in 35S-γ ⁎ plants and it is therefore possible that a small proportion of the β/γ dimers in the transgenic plants contain a WT γ subunit, making the dimer functional.…”
Section: Effectiveness Of the 35s-γ⁎ Approachmentioning
confidence: 92%
“…In mammals and insects it is known that a prenyl group is posttranslationally added (isoprenylation) to a CAAX motif on the C-terminus of the γ subunit and functions as a membrane anchor for the dimer (Matsuda et al, 1998). Studies have shown that isoprenylation of the γ subunit is essential for interactions with the plasma membrane (Simonds et al, 1991;GarciaHiguera et al, 1996;Lindorfer et al, 1996;Matsuda et al, 1998;Schillo et al, 2004), receptors (Simonds et al, 1991;Myung et al, 1999), and effectors (Simonds et al, 1991;Li et al, 1998;Matsuda et al, 1998;Murga et al, 1998), but not with the β subunit as dimerisation occurs before isoprenylation (Matsuda et al, 1998;Peskan and Oelmuller, 2000;Schillo et al, 2004). It is also known that β or γ subunits are unable to activate effectors individually (Murga et al, 1998;Yoshikawa et al, 2000), and free β or γ monomers are unstable or rapidly degraded by proteases (Simonds et al, 1991;Garcia-Higuera et al, 1998;Jin et al, 1998).…”
Section: Introductionmentioning
confidence: 95%
“…This motif is of great importance as it is the site where a prenyl group is post-translationally added to the poylpeptide, which occurs following the binding of a γ to a β subunit, and allows the heterodimer to be targeted to the endoplasmic reticulum prior to its subsequent anchorage at the plasma membrane (reviewed in Marrari et al, 2007). Dimerization between β and γ subunits is not dependent on isoprenylation (Schillo et al, 2004), but this lipidation is required for high affinity α-βγ and α-βγ-receptor interactions and effector activation (Myung et al, 2006, Myung et al, 1999.…”
Section: Protein Conservation and In Silico Analysesmentioning
confidence: 99%